Uruguay : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
The buffers built in the aftermath of Uruguay's 2002 banking crisis have shielded the financial sector from the effects of the global financial turmoil. Growth has been robust and the outlook continues to be favorable. However, inflation persists but capital inflows have improved, and policy measures have been taken in response. Uruguay exhibits no obvious signs of near-term domestic macrofinancial vulnerability. The external risks to the economy and the financial system come from a fragile global environment, and policy measures are recommended to reduce dollarization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet